Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
By forming an oxide coating layer including Ca, Bi, Ba, Ti and other elements on the core of the positive electrode active material of the sodium ion battery, the problem of low battery cycle performance caused by poor stability of the positive electrode active material is solved, and a higher Environmental stability, moisture resistance and cycling performance.
Patent Information
- Application Number
- CN202311038039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-17
AI Technical Summary
The existing positive electrode active materials have poor stability, resulting in low circulation performance of sodium ion batteries.
By forming a first cladding layer including MaOb on at least part of the core including NaxRy(PO4)z(P2O7)k, M includes Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, At least one of Mn, Ni or Co, the first covering layer composed of which can reduce the contact between the core and H2O, CO2, etc. in the air, thereby improving the environmental stability and moisture resistance of the material, thereby improving the cycling performance of the battery. .
The environmental stability and moisture resistance of the positive electrode active material are improved, the interface between the positive electrode active material and the electrolyte is stabilized, the circulation performance of the battery is improved, and the high first-circuit Coulomb efficiency is maintained.
Smart Images

Figure CN119495742A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are facing great challenges due to the increasing shortage of lithium resources, the rising prices of upstream materials, the lagging development of recycling technology, and the low recycling rate of old batteries. Sodium-ion batteries can use the sodium ion deintercalation process between the positive and negative electrodes to achieve charging and discharging. In addition, the reserves of sodium resources are far more abundant than lithium, the distribution is more extensive, and the cost is far lower than lithium. Therefore, sodium-ion batteries have become a new generation of electrochemical systems with great potential to replace lithium secondary batteries. However, due to the poor stability of existing positive electrode active materials, sodium-ion batteries have the problem of low cycle performance. Summary of the invention
[0003] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to improve the cycle performance of a battery containing the positive electrode active material.
[0004] In order to achieve the above-mentioned object, the present application provides a positive electrode active material in one aspect, wherein the positive electrode active material comprises:
[0005] The kernel includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤4, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, or Pb;
[0006] A first cladding layer, the first cladding layer is formed on at least a portion of the core, the first cladding layer comprising M a O b , M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12.
[0007] The present application at least includes the following beneficial effects: x R y (PO4) z (P2O7) k The core is formed at least partially including M a O bThe first coating layer, M includes at least one of Ca, Bi, Ba, Ti, Al, Mg, Fe, Cu, Zn, Mn, Ni or Co. The first coating layer of this composition can reduce the contact between the core and H2O, CO2 and the like in the air, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery. At the same time, the first coating layer can reduce the side reaction between the core surface and the electrolyte, stabilize the interface between the positive electrode active material and the electrolyte, improve the stability of the material, and further improve the cycle performance of the battery containing it. In addition, the first coating layer of this composition will not reduce the first cycle coulomb efficiency of the positive electrode active material, so that the battery maintains a high first cycle coulomb efficiency.
[0008] In some embodiments of the present application, the inner core includes at least one of Na4R3(PO4)2P2O7 or Na7V4(PO4)4P2O7, wherein R includes at least one of Fe, Ni, Co or Mn.
[0009] In some embodiments of the present application, M a O b Including TiO2, Al2O3, Nb2O5, MgO, Co3O4, CaTiO3, Bi4Ti3O 12 Or at least one of BaTiO3. Thus, the cycle performance of the battery containing it can be improved and the battery can maintain a high first-cycle coulomb efficiency.
[0010] In some embodiments of the present application, based on the total mass of the positive electrode active material, the content of the first coating layer is w%,
[0011] Based on the total mass of the core, the residual alkali content of the core is z%, 0.06≤z / w≤3, and can be optionally 0.06≤z / w≤1. Thus, the cycle performance of the battery containing the core can be improved and the battery can maintain a high first-cycle coulombic efficiency.
[0012] In some embodiments of the present application, 1%≤w%≤3%, and optionally 1.5%≤w%≤2.5%. Thus, the cycle performance of the battery containing the same can be improved and the battery can maintain a high first-cycle coulombic efficiency.
[0013] In some embodiments of the present application, 0.2%≤z%≤3%, optionally 0.2%≤z%≤0.6%.
[0014] In some embodiments of the present application, the thickness of the first coating layer is 1 nm-10 nm, and can be 2 nm-8 nm, thereby improving the cycle performance of the battery containing the first coating layer and maintaining a high first cycle coulombic efficiency of the battery.
[0015] In some embodiments of the present application, the positive electrode active material further includes a second coating layer, the second coating layer is formed on at least a portion of the core, the first coating layer is formed on at least a portion of the second coating layer, and the second coating layer includes carbon. Thus, the environmental stability, moisture resistance and conductivity of the positive electrode active material can be improved, thereby improving the kinetic performance and cycle performance of the battery containing the positive electrode active material.
[0016] In some embodiments of the present application, based on the total mass of the positive electrode active material, the carbon content in the second coating layer is n%, 0.16≤n / w≤1.5, and optionally 0.32≤n / w≤0.8. Thus, the environmental stability, moisture resistance and conductivity of the positive electrode active material can be improved, thereby improving the kinetic performance and cycle performance of the battery containing the same.
[0017] In some embodiments of the present application, 0.5%≤n%≤1.5%, optionally 0.8%≤n%≤1.2%. Thus, the environmental stability, moisture resistance and conductivity of the positive electrode active material can be improved, thereby improving the kinetic performance and cycle performance of the battery containing the positive electrode active material.
[0018] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions:
[0019] The volume average particle size Dv50 of the positive electrode active material is 2 μm-8 μm, and can be 2 μm-5 μm;
[0020] The Dv99 of the positive electrode active material is 10 μm-40 μm, and can be optionally 15 μm-30 μm;
[0021] The BET specific surface area of the positive electrode active material is 3 m 2 / g-11m 2 / g, optional 7m 2 / g-10m 2 / g;
[0022] The compaction density of the positive electrode active material under a pressure of 100 MPa is 1.3 g / cm 3 -2.1g / cm 3 , optional 1.7g / cm 3 -1.9g / cm 3 .
[0023] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising:
[0024] A core material is provided, the core material comprising Na x R y (PO4) z (P2O7)k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, or Pb;
[0025] The core material and M a O b Mixed sintering, M includes at least one of Ti, Al, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12, to obtain a positive electrode active material.
[0026] Therefore, the method of the present application can be used in the Na x R y (PO4) z (P2O7) k The core is formed including M a O b The first coating layer (M includes at least one of Ti, Al, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12), the first coating layer of this composition can reduce the contact between the inner core and H2O, CO2 and the like in the air, thereby improving the environmental stability and moisture resistance of the material, and then improving the cycle performance of the battery containing the same, and the first coating layer of this composition will not deteriorate the first-cycle coulomb efficiency of the positive electrode active material, thereby allowing the battery to maintain a higher first-cycle coulomb efficiency.
[0027] In some embodiments of the present application, the sintering temperature is 250° C.-550° C., and the holding time is 2 h-8 h.
[0028] In some embodiments of the present application, when the core material is mixed with M a O b Before mixed sintering, the core material is mixed with a carbon source and sintered in advance, thereby forming a second carbon-containing coating layer on the surface of the core material, improving the environmental stability, moisture resistance and conductivity of the positive electrode active material, thereby improving the cycle performance and kinetic performance of the battery containing the same.
[0029] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material obtained by the method described in the second aspect of the present application.
[0030] The fourth aspect of the present application provides a battery, which includes the positive electrode plate described in the third aspect of the present application.
[0031] In some embodiments of the present application, the battery comprises a sodium ion battery.
[0032] The fifth aspect of the present application provides an electrical device, which includes the battery described in the fourth aspect of the present application.
[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0035] Figure 1 Schematic diagram of a positive electrode active material according to an embodiment of the present application.
[0036] Figure 2 Schematic diagram of a positive electrode active material according to another embodiment of the present application.
[0037] Figure 3 is a schematic diagram of a battery according to one embodiment of the present application.
[0038] Figure 4 yes Figure 3 An exploded view of a battery according to an embodiment of the present application is shown.
[0039] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0040] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0041] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0042] Figure 8 Schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.
[0043] Fig. 9 It is an XRD comparison diagram of the positive electrode active materials of Example 1 and Comparative Example 1 of the present application.
[0044] Fig.10 This is a distribution diagram of the Ti element in the EDS spectrum of the positive electrode active material of Example 1 of the present application.
[0045] Description of reference numerals:
[0046] 1 battery; 11 shell; 12 electrode assembly; 13 cover plate; 2 battery module; 3 battery pack; 31 upper box; 32 lower box; 20 positive electrode active material; 21 kernel; 22 first coating layer; 23 second coating layer. DETAILED DESCRIPTION
[0047] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0048] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0053] With the technological development and increasing demand for electric vehicles and rechargeable mobile devices, secondary batteries, as a representative of the new energy field, have also seen rapid development in related research. Compared with traditional lithium-ion batteries, sodium-ion batteries have a strong price advantage and have broad application prospects in large-scale power storage systems.
[0054] Polyanion phosphate cathode materials have become one of the most popular cathode active materials for sodium ion batteries due to their abundant resources, environmental friendliness, ease of large-scale production, open sodium ion diffusion channels, and good thermal stability. However, due to process and formulation reasons, residual alkali (including sodium bicarbonate and sodium carbonate, etc.) is present on the surface of polyanion phosphate cathode materials. The residual alkali on the surface is easy to react with H2O, CO2, etc. in the air, resulting in poor environmental stability and moisture resistance of the materials, thereby reducing the battery cycle performance.
[0055] This application includes Na x R y (PO4) z (P2O7) k The core is formed at least partially including M a O b The first coating layer, M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co. The first coating layer of this composition can reduce the contact between the core and H2O, CO2 and the like in the air, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery. At the same time, the first coating layer can reduce the side reaction between the core surface and the electrolyte, stabilize the interface between the positive electrode active material and the electrolyte, improve the stability of the material, and further improve the cycle performance of the battery containing it. In addition, the first coating layer of this composition will not reduce the first-cycle coulomb efficiency of the positive electrode active material, so that the battery maintains a high first-cycle coulomb efficiency.
[0056] The positive electrode active material disclosed in the embodiment of the present application is suitable for sodium ion batteries, and the battery disclosed in the embodiment of the present application can be used in various energy storage systems that use batteries as power sources or use batteries as energy storage elements. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0057] The first aspect of the present application proposes a positive electrode active material, referring to Figure 1 The positive electrode active material 20 includes a core 21 and a first coating layer 22, wherein the core includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤4, 1≤k≤4, R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W or Pb, the first coating layer 22 is formed on at least a portion of the core 21, and the first coating layer 22 includes M a O b , M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12.
[0058] The present application at least includes the following beneficial effects: x R y (PO4) z (P2O7) k At least a portion of the core 21 is formed including M a O b The first coating layer 22, M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co. The first coating layer 22 of this composition can reduce the contact between the core 21 and H2O, CO2 and the like in the air, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery. At the same time, the first coating layer 22 can reduce the side reaction between the surface of the core 21 and the electrolyte, stabilize the interface between the positive electrode active material 20 and the electrolyte, improve the stability of the material, and further improve the cycle performance of the battery containing it. In addition, the first coating layer 22 of this composition will not reduce the first-cycle coulomb efficiency of the positive electrode active material 20, so that the battery maintains a high first-cycle coulomb efficiency.
[0059] In some embodiments of the present application, the Na x R y (PO4) z (P2O7) k 1≤x≤7, for example, x is 2≤x≤6, 3≤x≤5, 3≤x≤4, etc. Therefore, the core 21 includes this content of sodium ions, which can increase the gram capacity of the battery, so that the battery has a higher capacity.
[0060] In some embodiments of the present application, the Na x R y (PO4) z (P2O7) k R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W or Pb, and 1≤y≤4, for example, 2≤x≤4, 3≤x≤4, etc. Thus, the positive electrode active material composed of the present application has the advantages of chemical stability, thermal stability, electrochemical stability and high specific capacity.
[0061] In some embodiments of the present application, the Na x R y (PO4) z (P2O7) k , 1≤z≤4, 1≤k≤4, for example, 2≤z≤4, 3≤z≤4, etc., 2≤k≤4, 3≤k≤4, etc.
[0062] As an example, the Na x R y (PO4) z (P2O7) k It can include Na4Fe3(PO4)2P2O7, Na4Ni3(PO4)2P2O7, Na4Co3(PO4)2P2O7, Na4Mn3(PO4)2P2O7, Na7V4(PO4)4P2O7, Na 4.02 Fe 2.85 (PO4)2P2O7、Na4Fe 2.9 Mg 0.1 (PO4)2P2O7、Na4Fe 2.95 Al 0.05 (PO4)2P2O7 or Na4Fe 2.99 Cu 0.01 At least one of (PO4)2P2O7.
[0063] In other embodiments of the present application, the core 21 includes at least one of Na4R3(PO4)2P2O7 or Na7V4(PO4)4P2O7, wherein R includes at least one of Fe, Ni, Co or Mn, such as Na4Fe3(PO4)2P2O7, Na4Ni3(PO4)2P2O7, Na4Co3(PO4)2P2O7, Na4Mn3(PO4)2P2O7. Thus, by using the core 21 of this composition, the gram capacity of the positive electrode active material 20 can be increased, thereby increasing the capacity of the battery containing it.
[0064] It should be noted that the battery will be accompanied by Na deintercalation and consumption during the charge and discharge process, and the molar content of Na is different when the battery is discharged to different states. In the enumeration of the core 21 in this application, the molar content of Na is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and after the charge and discharge cycle, the molar content of Na will change.
[0065] In the enumeration of the core 21 in the present application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0066] In some embodiments of the present application, the first coating layer 22 is formed on at least a portion of the core 21, and the first coating layer 22 includes M a O b , M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12, for example, a is 2≤a≤6, 3≤a≤5, 3≤a≤4, etc. Therefore, the present application includes Na x R y (PO4) z (P2O7) k The core 21 is formed at least partially with the above-mentioned composition M a O b The first coating layer 22 of the composition can reduce the contact between the core 21 and H2O, CO2, etc. in the air, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery. At the same time, the first coating layer 22 can reduce the side reaction between the surface of the core 21 and the electrolyte, stabilize the interface between the positive electrode active material 20 and the electrolyte, improve the stability of the material, and further improve the cycle performance of the battery containing it. In addition, the first coating layer 22 of the composition will not reduce the first cycle coulomb efficiency of the positive electrode active material 20, so that the battery maintains a high first cycle coulomb efficiency.
[0067] As an example, M a O bIt may include at least one of CaO, Bi2O3, BaO, TiO2, Al2O3, Nb2O5, MgO, FeO, CuO, ZnO, MnO2, NiO or Co3O4.
[0068] In some embodiments of the present application, the M a O b Can include TiO2, Al2O3, Nb2O5, MgO, Co3O4, CaTiO3, Bi4Ti3O 12 Or at least one of BaTiO3. Therefore, the present application forms a first coating layer 22 of the above composition on the core 21. The first coating layer 22 of the composition can reduce the contact between the core 21 and H2O, CO2, etc. in the air, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery. At the same time, the first coating layer 22 can reduce the side reaction between the surface of the core 21 and the electrolyte, stabilize the interface between the positive electrode active material 20 and the electrolyte, improve the stability of the material, and further improve the cycle performance of the battery containing it. In addition, the first coating layer 22 of the composition will not reduce the first-cycle coulomb efficiency of the positive electrode active material 20, so that the battery maintains a high first-cycle coulomb efficiency.
[0069] In some embodiments of the present application, based on the total mass of the positive electrode active material 20, the content of the first coating layer 22 is w%; based on the total mass of the inner core 21, the residual alkali content of the inner core 21 is z%, 0.06≤z / w≤3, for example, 0.08≤z / w≤3, 0.1≤z / w≤3, 0.2≤z / w≤2.8, 0.5≤z / w≤2.5, 0.7≤z / w≤2.2, 1≤z / w≤2, 1.2≤z / w≤1.8, 1.5≤z / w≤1.7, etc. Specifically, due to the process, formula and other reasons, residual alkali (residual alkali includes sodium bicarbonate and sodium carbonate, etc.) is left on the surface of the inner core 21, and the residual alkali on the surface is easy to react with H2O, CO2 and the like in the air, resulting in poor environmental stability and moisture resistance of the material. The present application controls the content w% of the first coating layer 22 and the residual alkali amount z% of the inner core 21 to meet the above ratio, which can significantly improve the environmental stability and moisture resistance of the material, thereby improving the cycle performance of the battery. In other embodiments of the present application, the content w% of the first coating layer 22 and the residual alkali amount z% of the inner core 21 satisfy 0.06≤z / w≤1.
[0070] In the present application, the test of the residual alkali content z% of the core 21 can be measured by instruments and methods known in the art. For example, the free sodium in the core of the positive active material of the sodium ion battery can be tested with reference to GB / T9725-2007 "General Rules for Chemical Reagent Potentiometric Titration" for the test of free lithium, and the test results are converted according to the ratio of the molecular weight of residual sodium and residual lithium. For example, the molecular weight of NaHCO3 is 84, the molecular weight of LiHCO3 is 68, and the free lithium content obtained by the test result is 0.1%. According to the ratio of the molecular weight of NaHCO3 to LiHCO3, the free sodium content of the positive electrode material is converted to 0.124%. The method for testing the free lithium content of the positive electrode material in GB / T9725-2007 "General Rules for Chemical Reagent Potentiometric Titration" is: sampling and preparing the test solution according to the provisions of the product standard. Insert the specified electrode, start the electromagnetic stirrer, and titrate with the specified standard titration solution. Add about 90% of the required titration volume of standard titration solution from the burette and measure the potential or pH value of the solution. Measure the potential or pH value every time 1 mL or an appropriate amount of standard titration solution is added. Before and after the stoichiometric point, measure once every time 0.1 mL of standard titration solution is added. Continue titrating until the potential or pH value does not change much. Record the reading of the burette and the measured potential or pH value after each addition of the standard titration solution, and use the graphical method or the second-order derivative method to determine the titration endpoint.
[0071] In some embodiments of the present application, based on the total mass of the positive electrode active material 20, the content w% of the first coating layer 22 satisfies 1%≤w%≤3%, for example, 1.2%≤w%≤2.8%, 1.5%≤w%≤2.5%, 1.7%≤w%≤2.2%, 1.8%≤w%≤2%, etc. Therefore, the content w% of the first coating layer 22 of the present application satisfies the above conditions, which can improve the environmental stability and moisture resistance of the material, thereby improving the cycle performance of the battery. At the same time, the first coating layer 22 of this content can reduce the side reaction between the surface of the core 21 and the electrolyte, stabilize the interface between the positive electrode active material 20 and the electrolyte, improve the stability of the material, and thereby improve the cycle performance of the battery containing it. In addition, the first coating layer 22 of this content will not reduce the first cycle coulomb efficiency of the positive electrode active material 20, so that the battery maintains a high first cycle coulomb efficiency. In some other embodiments of the present application, based on the total mass of the positive electrode active material 20 , the content w% of the first coating layer 22 satisfies 1.5%≤w%≤2.5%.
[0072] In some embodiments of the present application, based on the total mass of the core 21, the residual alkali content z% of the core 21 satisfies 0.2%≤z%≤3%, for example, 0.5%≤z%≤2.8%, 0.8%≤z%≤2.5%, 1%≤z%≤2.2%, 1.2%≤z%≤2%, 1.5%≤z%≤1.8%, etc. Thus, the residual alkali content z% of the core 21 of the present application satisfies the above conditions, which can reduce the decomposition and gas production of residual alkali during the battery cycle, reduce battery flatulence, and thus improve the battery cycle performance. In some embodiments of the present application, based on the total mass of the positive active material 20, the residual alkali content z% of the core 21 satisfies 0.2%≤z%≤0.6%.
[0073] In some embodiments of the present application, the thickness of the first coating layer 22 can be 1nm-10nm, such as 2nm-9nm, 3nm-8nm, 4nm-7nm, 5nm-6nm, etc. Therefore, the thickness of the first coating layer 22 of the present application meets the above conditions, which can improve the environmental stability and moisture resistance of the material, thereby improving the cycle performance of the battery. At the same time, the first coating layer 22 of this thickness can reduce the side reaction between the surface of the core 21 and the electrolyte, stabilize the interface between the positive electrode active material 20 and the electrolyte, improve the stability of the material, and thereby improve the cycle performance of the battery containing it. In addition, the first coating layer 22 of this thickness will not reduce the first cycle coulomb efficiency of the positive electrode active material, so that the battery maintains a higher first cycle coulomb efficiency. In other embodiments of the present application, the thickness of the first coating layer 22 is 2nm-8nm.
[0074] In some embodiments of the present application, reference Figure 2 The positive electrode active material 20 further includes a second coating layer 23, the second coating layer 23 is formed on at least a portion of the core 21, the first coating layer 22 is formed on at least a portion of the second coating layer 23, and the second coating layer 23 includes carbon. Thus, by coating the outer surface of the core 21 with the second coating layer 23 including carbon, the second coating layer 23 can not only improve the environmental stability and moisture resistance of the core 21, but also improve the conductivity of the core 21, thereby improving the kinetic performance and cycle performance of the battery containing the same.
[0075] In some embodiments of the present application, based on the total mass of the positive electrode active material 20, the carbon content in the second coating layer 23 is n%, 0.16≤n / w≤1.5, for example, 0.18≤n / w≤1.5, 0.2≤n / w≤1.5, 0.25≤n / w≤1.5, 0.3≤n / w≤1.5, 0.35≤n / w≤1.45, 0.4≤n / w≤1.4, 0.45≤n / w≤1.35, 0.5≤n / w≤1.3, 0.55≤n / w≤1.25, 0.6≤n / w≤1.2, 0.65≤n / w≤1.1, 0.7≤n / w≤1, 0.8≤n / w≤0.9, 0.85≤n / w≤0.9, etc. Thus, the carbon content n% in the second coating layer 23 of the present application and the content w% of the first coating layer 22 are controlled within the above range, which can significantly improve the environmental stability, moisture resistance and conductivity of the positive electrode active material 20, thereby improving the kinetic performance and cycle performance of the battery containing the positive electrode active material 20. In other embodiments of the present application, based on the total mass of the positive electrode active material 20, the carbon content n% in the second coating layer 23 satisfies 0.32≤n / w≤0.8.
[0076] In some embodiments of the present application, based on the total mass of the positive electrode active material 20, the carbon content in the second coating layer 23 is n%, 0.5%≤n%≤1.5%, for example, 0.6%≤n%≤1.4%, 0.7%≤n%≤1.3%, 0.8%≤n%≤1.3%, 0.9%≤n%≤1.2%, 1%≤n%≤1.1%, etc. Therefore, the carbon content n% in the second coating layer 23 of the present application is controlled within the above range, which can significantly improve the environmental stability, moisture resistance and conductivity of the positive electrode active material 20, thereby improving the kinetic performance and cycle performance of the battery containing it. In other embodiments of the present application, based on the total mass of the positive electrode active material 20, the carbon content n% in the second coating layer 23 satisfies 0.8%≤n%≤1.2%.
[0077] In some embodiments of the present application, the volume average particle size Dv50 of the positive electrode active material 20 is 2μm-8μm, for example, the Dv50 of the positive electrode active material can be 2.5μm-7.5μm, 3μm-7μm, 3.5μm-6.5μm, 4μm-6μm, 4.5μm-5.5μm, 4.8μm-5μm, etc. In other embodiments of the present application, the volume average particle size Dv50 of the positive electrode active material 20 is 2μm-5μm.
[0078] In some embodiments of the present application, the Dv99 of the positive electrode active material 20 is 10μm-40μm, for example, the Dv99 of the positive electrode active material can be 12μm-37μm, 15μm-35μm, 18μm-32μm, 20μm-30μm, 22μm-28μm, 23μm-25μm, etc. In other embodiments of the present application, the Dv99 of the positive electrode active material 20 is 15μm-30μm.
[0079] In the present application, the volume average particle size Dv50 refers to the particle size corresponding to the cumulative volume distribution percentage of 50%, and Dv99 refers to the particle size corresponding to the cumulative volume distribution percentage of 99%. For example, the test method of the volume average particle size Dv50 and Dv99 can refer to the standard GB / T 19077-2016 and be measured using a laser particle size analyzer (e.g., MalvernMaster Size3000).
[0080] In some embodiments of the present application, the BET specific surface area of the positive electrode active material 20 is 3 m 2 / g-11m 2 / g, for example, the BET specific surface area of the positive electrode active material 20 may be 4 m 2 / g-10m 2 / g,5m 2 / g-9m 2 / g,6m 2 / g-8m 2 / g,7m 2 / g-7.5m 2 In some other embodiments of the present application, the BET specific surface area of the positive electrode active material 20 is 7 m 2 / g-10m 2 / g.
[0081] In the present application, the BET specific surface area of the positive electrode active material 20 has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, it can be tested by referring to the following method: using the American Micromeritics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390, take about 7g of the sample and put it into a 9cc long tube with a bulb, degas at 200°C for 2h, and then put it into the main machine for testing to obtain the BET specific surface area data of the positive electrode active material 20.
[0082] In some embodiments of the present application, the compaction density of the positive electrode active material 20 at a pressure of 100 MPa is 1.3 g / cm 3 -2.1g / cm 3 For example, the compaction density of the positive electrode active material 20 at a pressure of 100 MPa may be 1.4 g / cm3 -2g / cm 3 , 1.5g / cm 3 -1.9g / cm 3 , 1.6g / cm 3 -1.8g / cm 3 , 1.7g / cm 3 -1.8g / cm 3 In some embodiments of the present application, the compaction density of the positive electrode active material 20 under a pressure of 100 MPa is 1.7 g / cm 3 -1.9g / cm 3 .
[0083] In the present application, "compacted density" has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, the following test method can be used: a certain amount of powder m is placed in a special compaction mold, the mold is placed on a compaction density instrument, a pressure of 100 MPa is set, and the thickness and volume v of the powder under a pressure of 300 MPa is measured on the equipment. The compacted density is calculated by density = mass m / volume v; (for details, refer to GB / T24533-2009).
[0084] Specifically, when at least one of the volume average particle size Dv50, volume average particle size Dv99, specific surface area and compaction density under a pressure of 100 MPa of the positive electrode active material 20 of the present application is within the above range, the conduction distance within the positive electrode active material 20 is small and the surface side reactions are small, which promotes the positive electrode active material 20 to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0085] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0086] S100: Provide core materials
[0087] In some embodiments of the present application, the core material includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W or Pb.
[0088] S200: The core material and M a O b Mixed sintering
[0089] In some embodiments of the present application, the core material of step S100 is mixed with M a O b Mixed sintering, the surface of the core material is coated with M a O b The first coating layer, M includes at least one of Ti, Al, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12, to obtain a positive electrode active material. Specifically, during the sintering process, free sodium ions (residual alkali) on the surface of the core material will enter the crystal structure of the core material, thereby increasing the sodium ions in the core material. Therefore, the sintering process forms M a O b The first coating layer does not deteriorate the first cycle coulombic efficiency of the positive electrode active material.
[0090] As an example, the core material is uniformly mixed with a solvent such as anhydrous ethanol, and then M is added. a O b After mixing evenly, the solvent is evaporated off by vacuum evaporation (70°C-100°C, for example, 70°C, 80°C, 90°C or 100°C) using a rotary evaporator, and then the filter cake is washed several times using a suction filtration device, and the filter cake is dried in a vacuum oven, and then the powder material is calcined at 250°C-550°C in a nitrogen atmosphere for 2h-8h to form a M-containing a O b For example, the sintering temperature may be 300°C-500°C, 350°C-450°C, 350°C-400°C, etc. The sintering time may be 3h-7h, 4h-6h, 5h-6h, etc. At the sintering temperature, a dense first coating layer may be formed on the surface of the inner core, thereby improving the environmental stability and moisture resistance of the material, and further improving the cycle performance of the battery containing the same.
[0091] In some embodiments of the present application, when the core material is mixed with M a O b Before mixed sintering, the core material is mixed with a carbon source and sintered in advance, so that a second carbon-containing coating layer can be formed on the surface of the core material, thereby improving the environmental stability, moisture resistance and conductivity of the positive electrode active material, thereby improving the cycle performance and kinetic performance of the battery containing it.
[0092] In some embodiments of the present application, the core material is mixed with a carbon source and sintered under nitrogen as a protective gas, the temperature is raised to 500°C-600°C, for example, 520°C-580°C, 540°C-560°C, and the sintering is carried out for 6h-14h, for example, 7h-13h, 8h-12h, 9h-11h, 10h-11h. As the non-carbon elements in the carbon source are removed, a second carbon-containing coating layer is formed on the surface of the core material.
[0093] As an example, the carbon source may include at least one of sucrose, tannic acid, polyethylene glycol, polyvinyl pyrrolidone, glucose, ascorbic acid, or citric acid.
[0094] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material obtained by the method described in the second aspect of the present application.
[0095] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material mentioned above or the positive electrode active material obtained by the method described above.
[0096] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0097] In some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite negative electrode current collector. For example, as the metal foil, aluminum foil may be used. The composite negative electrode current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) on a substrate.
[0098] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.
[0099] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0100] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0101] A fourth aspect of the present application provides a battery, which includes the positive electrode plate described in the third aspect of the present application.
[0102] In some embodiments of the present application, the battery comprises a sodium ion battery.
[0103] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0104] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes the polymer described in the first aspect of the present application.
[0105] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0106] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) on a substrate.
[0107] In some embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites or silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds or tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0108] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0109] In some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).
[0110] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0111] The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0112] In some embodiments of the present application, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0113] In some embodiments of the present application, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate or sodium bis(trifluoromethylsulfonyl)imide.
[0114] In some embodiments of the present application, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.
[0115] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0116] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0117] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0118] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0119] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0120] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0121] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 3 The battery cell 1 is a square structure as an example.
[0122] In some embodiments, reference Figure 4 The outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0123] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0124] Figure 5 2 is an example of a battery module 2. Figure 5 In the battery module 2, the plurality of battery cells 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 1 may be fixed by fasteners.
[0125] Optionally, the battery module 2 may further include a housing having a receiving space, and the plurality of battery cells 1 are received in the receiving space.
[0126] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0127] Figure 6 and Figure 7 The battery pack 3 is used as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 can cover the lower box body 32 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0128] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0129] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0130] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0131] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery may be used as a power source.
[0132] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0133] Example 1
[0134] 1. Preparation of positive electrode sheet
[0135] (1) Preparation of positive electrode active materials
[0136] Na4Fe3(PO4)2P2O7 material is evenly mixed in anhydrous ethanol solvent, and titanium dioxide sol is added, wherein the mass ratio of Na4Fe3(PO4)2P2O7 material to solvent is 80:200, and the solvent is evaporated out by vacuum evaporation (80°C) using a rotary evaporator, and then the material is washed with a suction filtration device, and the filter cake is dried in a vacuum oven, and then the powder material is calcined at 300°C for 6 hours in a nitrogen atmosphere. After natural cooling, a first coating layer including titanium dioxide is formed on the surface of the Na4Fe3(PO4)2P2O7 material, i.e., the positive electrode active material.
[0137] (2) Preparation of positive electrode sheet
[0138] The polyvinylidene fluoride binder is fully dissolved in N-methylpyrrolidone, and a carbon black conductive agent and a positive electrode active material are added to prepare a uniformly dispersed slurry, wherein the mass ratio of the polyvinylidene fluoride binder to the carbon black conductive agent and the positive electrode active material is 10:20:70. The slurry is evenly coated on both sides of the aluminum foil, and then transferred to a vacuum drying oven for complete drying. The obtained electrode sheet is rolled and then punched to obtain a positive electrode sheet.
[0139] 2. Preparation of negative electrode sheet
[0140] The negative electrode active material hard carbon, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC-Na) are uniformly mixed in a proper amount of solvent deionized water at a mass ratio of 96:1.5:1.5:1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on both sides of the negative electrode collector copper foil. Through drying and cold pressing, a negative electrode active material layer is formed on both sides of the negative electrode collector. Finally, after striping and cutting processes, a negative electrode sheet is obtained.
[0141] 3. Preparation of electrolyte
[0142] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), fully dried electrolyte salt NaPF6 was dissolved in ethylene glycol dimethyl ether, and after mixing evenly, an electrolyte solution with a concentration of 0.5 mol / L was obtained.
[0143] 4. Isolation film
[0144] Polypropylene film is used as the isolation film.
[0145] 5. Preparation of secondary batteries
[0146] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried sodium ion battery. After vacuum packaging, standing, forming, and shaping processes, a sodium ion battery is obtained.
[0147] The preparation methods of the sodium ion batteries of Examples 2-35 and Comparative Example 1 are the same as that of Example 1, except that the compositions of the prepared positive electrode active materials are different, as shown in Table 1.
[0148] Embodiment 36
[0149] Preparation of negative electrode
[0150] Conductive agent carbon black (Super P) and binder styrene-butadiene rubber (SBR) were mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 1.5:1.5 to obtain a negative electrode slurry. The negative electrode slurry was coated on both sides of the negative electrode current collector copper foil, and a negative electrode active material layer was formed on both sides of the negative electrode current collector through drying and cold pressing. Finally, a negative electrode sheet was obtained through striping and cutting processes. The remaining steps such as the preparation of the positive electrode sheet, electrolyte, isolation membrane and sodium ion battery were the same as in Example 1.
[0151] The XRD comparison diagram of the positive electrode active material of Example 1 and Comparative Example 1 is as follows: Fig. 9 As shown by Fig. 9 It can be seen that the XRD patterns of the positive electrode active materials of Example 1 and Comparative Example 1 have the same peak position as the XRD pattern of the positive electrode active material of Comparative Example 1, indicating that coating the first coating layer on the outer surface of the inner core of Example 1 will not destroy the lattice structure of the inner core material, and because the amount of the first coating is small, the characteristic peak of the coating layer material does not appear in the XRD diffraction peak.
[0152] The distribution diagram of Ti element in the EDS spectrum of the positive electrode active material of Example 1 (refer to GB / T 17359-2012 test method) is as follows: Fig.10 As shown, it is shown that the Ti element is evenly distributed in the first coating layer on the surface of the positive electrode active material.
[0153]
[0154]
[0155] Embodiment 37
[0156] Preparation of positive electrode active materials
[0157] Na4R3(PO4)2P2O7 material is mixed with glucose and sintered. The temperature is raised to 550°C in nitrogen as a protective gas and kept warm for 4 hours. As the non-carbon elements in glucose are removed, a second carbon-containing coating layer is formed on the surface of the core material. The core forming the second coating layer is placed in anhydrous ethanol solvent and mixed evenly. Titanium dioxide sol is added, wherein the mass ratio of Na4R3(PO4)2P2O7 material to the solvent is 80:200. A rotary evaporator is used to vacuum evaporate the solvent (80°C), and then the material is washed with a suction filtration device. The filter cake is dried in a vacuum oven, and then the powder material is calcined at 300°C in a nitrogen atmosphere for 6 hours. After natural cooling, a first coating layer including titanium dioxide is formed on the surface of the second coating layer, i.e., the positive electrode active material.
[0158] The remaining steps such as the preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the isolation membrane and the sodium ion battery are the same as those in Example 1.
[0159] The preparation methods of the sodium ion batteries of Examples 38-44 and Comparative Example 2 are the same as that of Example 37, except that the compositions of the prepared positive electrode active materials are different, as shown in Table 2.
[0160] Embodiment 45
[0161] Preparation of negative electrode
[0162] Conductive agent carbon black (Super P) and binder styrene-butadiene rubber (SBR) are mixed evenly in a proper amount of solvent deionized water at a mass ratio of 1.5:1.5 to obtain a negative electrode slurry. The negative electrode slurry is coated on both sides of the negative electrode collector copper foil. A negative electrode active material layer is formed on both sides of the negative electrode collector through drying and cold pressing. Finally, the negative electrode sheet is obtained through striping and cutting processes. The remaining steps such as the preparation of the positive electrode sheet, electrolyte, isolation membrane and sodium ion battery are the same as those in Example 37.
[0163]
[0164] The environmental stability of the positive electrode active materials of Examples 1-45 and Comparative Examples 1-2, as well as the first-cycle coulombic efficiency and cycle performance of the obtained sodium ion batteries were characterized. The characterization results are shown in Table 3.
[0165] (1) Environmental stability of positive electrode active materials
[0166] The positive electrode active material is exposed to an environment at room temperature (humidity is about 10%), and the water content of the positive electrode active material is tested at 0 min and 60 min respectively. The specific test method can refer to the GB / T 11133-2015 test method.
[0167] (2) First-cycle Coulombic efficiency of sodium-ion batteries
[0168] The sodium ion secondary battery was charged at 0°C at a constant current of 1 / 3C to 3.75V, and then charged at a constant voltage of 3.75V until the current dropped to 0.05C. The first charge capacity (C c1 ); then discharge to 1.5V with a constant current of 1 / 3C to obtain the first discharge capacity (C d1 ), and calculate the first cycle coulombic efficiency of the sodium ion battery = first discharge capacity (Cd1) / first charge capacity (Cc1)*100%.
[0169] (3) Cyclic performance test:
[0170] The ambient temperature was controlled at 25°C, the battery was charged to 3.65V at 1C, then charged to 0.05C at a constant voltage, left to stand for 10 minutes, and then discharged to 1.5V at 1C. The discharge capacity was recorded as C0. 300 cycles were performed according to the above charge and discharge process. The discharge capacity of the 300th cycle was C1, and the cycle capacity retention rate of the battery cell = C1 / C0*100%.
[0171] Table 3
[0172]
[0173]
[0174] Conclusion: Comparing Examples 1-36 with Comparative Example 1, the water content of the positive electrode active materials of Examples 1-36 after 60 minutes is significantly lower than that of the positive electrode active materials of Comparative Example 1, indicating that the positive electrode active materials of Examples 1-36 have higher moisture resistance, and the first cycle coulomb efficiency and capacity retention rate of the corresponding batteries of Examples 1-36 are higher than those of Comparative Example 1. Comparing Examples 37-45 with Comparative Example 2, the water content of the positive electrode active materials of Examples 37-45 after 60 minutes is significantly lower than that of the positive electrode active materials of Comparative Example 1, indicating that the positive electrode active materials of Examples 37-45 have higher moisture resistance, and the first cycle coulomb efficiency and capacity retention rate of the corresponding batteries of Examples 37-45 are higher than those of Comparative Example 2. This shows that the positive electrode active materials of the present application have excellent moisture resistance and improve the first cycle coulomb efficiency and cycle performance of the battery containing them.
[0175] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: include: The kernel includes Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤4, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, or Pb; A first cladding layer, the first cladding layer is formed on at least a portion of the core, the first cladding layer comprising M a O b , M includes at least one of Ca, Bi, Ba, Ti, Al, Nb, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12.
2. The positive electrode active material according to claim 1, characterized in that The inner core includes at least one of Na4R3(PO4)2P2O7 or Na7V4(PO4)4P2O7, wherein R includes at least one of Fe, Ni, Co or Mn.
3. The positive electrode active material according to claim 1 or 2, characterized in that: M a O b Including TiO2, Al2O3, Nb2O5, MgO, Co3O4, CaTiO3, Bi4Ti3O 12 Or at least one of BaTiO3.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that Based on the total mass of the positive electrode active material, the content of the first coating layer is w%, Based on the total mass of the inner core, the residual alkali content of the inner core is z%, 0.06≤z / w≤3, and can be optionally 0.06≤z / w≤1.
5. The positive electrode active material according to claim 4, characterized in that 1%≤w%≤3%, optionally 1.5%≤w%≤2.5%.
6. The positive electrode active material according to claim 4, characterized in that 0.2%≤z%≤3%, optionally 0.2%≤z%≤0.6%.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The thickness of the first coating layer is 1 nm-10 nm, and can be optionally 2 nm-8 nm.
8. The positive electrode active material according to any one of claims 4 to 6, characterized in that The positive electrode active material further includes a second coating layer formed on at least a portion of the inner core, the first coating layer formed on at least a portion of the second coating layer, and the second coating layer includes carbon.
9. The positive electrode active material according to claim 8, characterized in that Based on the total mass of the positive electrode active material, the carbon content in the second coating layer is n%, 0.16≤n / w≤1.5, and optionally 0.32≤n / w≤0.
8.
10. The positive electrode active material according to claim 9, characterized in that 0.5%≤n%≤1.5%, optionally 0.8%≤n%≤1.2%.
11. The positive electrode active material according to any one of claims 1 to 10, characterized in that The positive electrode active material satisfies at least one of the following conditions: The volume average particle size Dv50 of the positive electrode active material is 2 μm-8 μm, and can be 2 μm-5 μm; The Dv99 of the positive electrode active material is 10 μm-40 μm, and can be optionally 15 μm-30 μm; The BET specific surface area of the positive electrode active material is 3 m 2 / g-11m 2 / g, optional 7m 2 / g-10m 2 / g; The compaction density of the positive electrode active material under a pressure of 100 MPa is 1.3 g / cm 3 -2.1g / cm 3 , optional 1.7g / cm 3 -1.9g / cm 3 .
12. A method for preparing a positive electrode active material, characterized in that: include: A core material is provided, the core material comprising Na x R y (PO4) z (P2O7) k , wherein 1≤x≤7, 1≤y≤4, 1≤z≤2, 1≤k≤4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, or Pb; The core material and M a O b Mixed sintering, M includes at least one of Ti, Al, Mg, Fe, Cu, Zn, Mn, Ni or Co, 1≤a≤7, 1≤b≤12, to obtain a positive electrode active material.
13. The method according to claim 12, characterized in that The sintering temperature is 250° C.-550° C., and the heat preservation time is 2 h-8 h.
14. The method according to claim 12 or 13, characterized in that In the case of mixing the core material with M a O b Before the mixed sintering, the core material and the carbon source are mixed and sintered in advance.
15. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 11 or the positive electrode active material obtained by the method according to any one of claims 12 to 14.
16. A battery, characterized in that: Including the positive electrode sheet as described in claim 15.
17. The battery according to claim 16, characterized in that The battery comprises a sodium ion battery.
18. An electrical device, characterized in that: A battery comprising the battery of claim 16 or 17.
Citation Information
Patent Citations
Positive electrode active material, electrochemical device, and electronic apparatus
CN113437275A
Positive electrode active material, electrochemical device, and electronic apparatus
CN114613954A
Positive electrode active material and preparation method thereof, positive electrode plate and lithium battery
CN115663165A
Cited By
Sodium-ion battery positive electrode material with core-shell structure and preparation method of sodium-ion battery positive electrode material
CN120784312A